2010
DOI: 10.1163/000579510x510511
|View full text |Cite
|
Sign up to set email alerts
|

Sex biased natal dispersal is not a fixed trait in a stable population of Seychelles warblers

Abstract: SummaryWe observed a change in the sex-specific rate of delayed natal dispersal in a stable population of Seychelles warblers over a period of 20 years. At first, females were more likely to delay dispersal in their first year of life than were males, whereas later there was no sex bias in the rate of delayed natal dispersal. Similarly, the female-bias in helping-at-the-nest and the male-bias in floating have also weakened over time. These changes may have resulted from the decrease in variation in territory q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 33 publications
0
35
0
1
Order By: Relevance
“…S e y c h e l l e s warblers were originally thought to be an exception in that females were more likely to delay dispersal and become subordinate helpers/cobreeders than males, with 88% of subordinates being female helpers/ cobreeders in 1986-1990(Komdeur 1996b. As mentioned above, this bias toward helpers being females decreased over time to 68% in later years (Richardson et al 2002 ) and subsequently disappeared altogether (Eikenaar et al 2010 ). Additionally, a small proportion of birds (14% of females and 3% of males) became subordinates, usually for the second time, after being deposed as dominant breeders.…”
Section: Helping Behaviormentioning
confidence: 69%
See 2 more Smart Citations
“…S e y c h e l l e s warblers were originally thought to be an exception in that females were more likely to delay dispersal and become subordinate helpers/cobreeders than males, with 88% of subordinates being female helpers/ cobreeders in 1986-1990(Komdeur 1996b. As mentioned above, this bias toward helpers being females decreased over time to 68% in later years (Richardson et al 2002 ) and subsequently disappeared altogether (Eikenaar et al 2010 ). Additionally, a small proportion of birds (14% of females and 3% of males) became subordinates, usually for the second time, after being deposed as dominant breeders.…”
Section: Helping Behaviormentioning
confidence: 69%
“…h i s w a s t h o u g h t t o b e b e c a u s e f e m a l e s a r e usually born on higher-quality territories than males (Komdeur et al 1997 , see "Sex allocation"), and as there is a positive correlation between the length of time for which independent of spring delay dispersal and the natal territory quality, females ended up delaying dispersal longer than males. h is sex-bias in dispersal behavior disappeared later in the study, however, apparently as a result of females starting to disperse earlier, rather than males delaying dispersal longer (Eikenaar et al 2007(Eikenaar et al , 2010.…”
Section: Group Livingmentioning
confidence: 81%
See 1 more Smart Citation
“…At that time there was male-biased dispersal and female-biased helping because females were usually born on higher quality territories than males (Komdeur et al, 1997), which delayed dispersal for a longer period than males and more often became helpers. Eikenaar et al (2010) show that over the last decades the territory quality gradient across the population had gradually flattened due to restoration of the island vegetation and its associated insect food, which resulted in a decline and eventually in an absence of sex-biased dispersal and helping. Fewer females delayed dispersal from high quality territories and fewer males dispersed from poor quality territories and more males became helpers.…”
Section: Interactions Between Environmental Heterogeneity Dispersal mentioning
confidence: 99%
“…Eikenaar et al (2010) demonstrated in the cooperatively breeding Seychelles warbler (Acrocephalus sechellensis) that both sex-specific natal dispersal and helping behaviour are biased in relation to a change in the distribution of insect food resources (territory quality) and not to changes in population size or density. The island warbler population has remained stable in size and density from 1985 onwards.…”
Section: Interactions Between Environmental Heterogeneity Dispersal mentioning
confidence: 99%